Biofeedback Acupoint Stimulation Combined with Rood Technique on Walking Function of Stroke Patients in Convalescent Period - MENG Haichao; QU Shujie; CHANG Yongxia; HAO Lisha; ZHAO Hailu; MA Qiuyun; ZUO Xiaohong; WANG Zhengtian (康复学报)
ObjectiveTo observe the effect of biofeedback acupoint stimulation combined with Rood technique on walking function of stroke patients in convalescent period.MethodsA total of 120 stroke patients in convalescent period hospitalized in the Rehabilitation Medicine Department of the First Affiliated Hospital of Hebei North University from January 2020 to January 2021 were randomly divided into control group and observation group, with 60 cases in each group. Both groups received routine medical treatment on improving cerebral circulation, protecting brain cells, maintaining water and electrolyte balance, and also received routine rehabilitation training such as occupational therapy, physical therapy, and psychotherapy. The control group received Rood technique plus routine treatment and rehabilitation training. The Rood technique included sensory stimulation induced muscle response training, sensory stimulation inhibited muscle response training, the individual development principle guided motor control ability training, once a day, 40 minutes a time, five days a week, lasting for four weeks. The observation group received biofeedback acupoint stimulation in addition to the treatment provided to the control group. Zusanli (ST 36), Yanglingquan (GB 34), Jiexi (ST 41) and Shangjuxu (ST 37) acupoints were selected, the stimulation frequency was set at 50 Hz, lasting for 4 seconds, and the stimulation interval was once every 12 seconds. The intensity was adjusted between 20~60 mA, according to the patients' tolerance level. The stimulation protocol was given once a day, 15 minutes a time, five times a week for four weeks. Before treatment and four weeks after treatment, 10-meter walking test (10MWT), 6 minute walking test (6MWT), time up and go (TUG) and functional ambulation category (FAC) were used to evaluate patients' walking function; the surface electromyographic signals (iMEG, RMS) of the tibialis anterior muscle was used to evaluate the condition of the patients' tibialis anterior muscle.ResultsCompared with that before treatment, TUG of both groups after treatment decreased significantly, 10MWT and 6MWT increased significantly, and the differences were statistically significant (P<0.05). Compared with the control group, TUG in the observation group were significantly lower, 10MWT and 6MWT were significantly higher, and the differences were statistically significant (P<0.05). Compared with that before treatment, the FAC of both groups after treatment significantly improved, and the differences were statistically significant (P<0.05); compared with the control group, the FAC of the observation group improved more significantly, and the difference was statistically significant (P<0.05). Compared with that before treatment, iEMG of tibialis anterior muscle was significantly higher and RMS was significantly lower in both groups after treatment, and the differences were statistically significant (P<0.05); compared with the control group, iEMG of tibialis anterior muscle was significantly higher and RMS was significantly lower in the observation group, and the differences were statistically significant (P<0.05).ConclusionBiofeedback acupoint stimulation combined with Rood technique can improve walking function and tibialis anterior muscle function in stroke patients during convalescence.